A hybrid catalytic hydrogenation/membrane distillation process for nitrogen resource recovery from nitrate-contaminated waste ion exchange brine. (15th May 2020) - Huo, Xiangchen; Vanneste, Johan; Cath, Tzahi Y.; Strathmann, Timothy J.
Abstract: Ion exchange is widely used to treat nitrate-contaminated groundwater, but high salt usage for resin regeneration and management of waste brine residuals increase treatment costs and add environmental burdens. Development of palladium-based catalytic nitrate treatment systems for brine treatment and reuse has showed promising activity for nitrate reduction and selectivity towards the N2 over the alternative product ammonia, but this strategy overlooks the potential value of nitrogen resources. Here, we evaluated a hybrid catalytic hydrogenation/membrane distillation process for nitrogen resource recovery during treatment and reuse of nitrate-contaminated waste ion exchange brines. In the first step of the hybrid process, a Ru/C catalyst with high selectivity towards ammonia was found to be effective for nitrate hydrogenation under conditions representative of waste brines, including expected salt buildup that would occur with repeated brine reuse cycles. The apparent rate constants normalized to metal mass (0.30 ± 0.03 mM min −1 gRu −1 under baseline condition) were comparable to the state-of-the-art bimetallic Pd catalyst. In the second stage of the hybrid process, membrane distillation was applied to recover the ammonia product from the brine matrix, capturing nitrogen as ammonium sulfate, a commercial fertilizer product. Solution pH significantly influenced the rate of ammonia mass transfer through the gas-permeable membrane by controlling the fraction of free ammonia species (NH3 ) present in the solution. The rate of ammonia recovery was not affected by increasing salt levels in the brine, indicating the feasibility of membrane distillation for recovering ammonia over repeated reuse cycles. Finally, high rates of nitrate hydrogenation (apparent rate constant 1.80 ± 0.04 mM min −1 gRu −1 ) and ammonia recovery (overall mass transfer coefficient 0.20 m h −1 ) with the hybrid treatment process were demonstrated when treating a real waste ion exchange brine obtained from a drinking water utility. These findings introduce an innovative strategy for recycling waste ion exchange brine while simultaneously recovering potentially valuable nitrogen resources when treating contaminated groundwater. Graphical abstract: Image 1 Highlights: Introduce a hybrid ion exchange/catalytic hydrogenation/membrane distillation process. Ru/C shows high activity for selective nitrate reduction to ammonia. Membrane distillation used to recover ammonia product as a fertilizer. Nitrate hydrogenation and ammonia recovery demonstrated with real IX waste brine.